More Than Virality: Online Sharing of Controversial News With Activated Audience. (March 2020) - Kim, Eun-mee; Ihm, Jennifer
In contrast to earlier studies that focus on virality, we examine how individuals share controversial news online by accounting for audience features. The results from surveys of 400 individuals suggest that they are more likely to share highly controversial news (a) on open, asymmetrical social media or (b) with communication partners with a low frequency rather than a high frequency, but are more likely to share moderately controversial news (c) on closed, symmetrical social media. This study implies that interpersonal motives determine the online path of controversial news and that media environments play unique roles in moderating and spreading controversies in society.